Nerandomilast in patients with idiopathic pulmonary fibrosis - Richeldi,L; Azuma,A; Cottin,V; Kreuter,M; Maher,TM; Martinez,FJ; Oldham,JM; Valenzuela,C; Clerisme-Beaty,E; Gordat,M; Wachtlin,D; Liu,Y; et al. (New England Journal of Medicine, 2025)
BackgroundNerandomilast (BI 1015550) is an orally administered preferential inhibitor of phosphodiesterase 4B with antifibrotic and immunomodulatory effects. In a phase 2 trial involving patients with idiopathic pulmonary fibrosis, treatment with nerandomilast stabilized lung function over a period of 12 weeks.MethodsIn this phase 3, double-blind trial, we randomly assigned patients with idiopathic pulmonary fibrosis in a 1:1:1 ratio to receive nerandomilast at a dose of 18 mg twice daily, nerandomilast at a dose of 9 mg twice daily, or placebo, with stratification according to background antifibrotic therapy (nintedanib or pirfenidone vs. none). The primary end point was the absolute change from baseline in forced vital capacity (FVC), measured in milliliters, at week 52.ResultsA total of 1177 patients underwent randomization, of whom 77.7% were taking nintedanib or pirfenidone at enrollment. Adjusted mean changes in FVC at week 52 were −114.7 ml (95% confidence interval [CI], −141.8 to −87.5) in the nerandomilast 18-mg group, −138.6 ml (95% CI, −165.6 to −111.6) in the nerandomilast 9-mg group, and −183.5 ml (95% CI, −210.9 to −156.1) in the placebo group. The adjusted difference between the nerandomilast 18-mg group and the placebo group was 68.8 ml (95% CI, 30.3 to 107.4; P<0.001), and the adjusted difference between the nerandomilast 9-mg group and the placebo group was 44.9 ml (95% CI, 6.4 to 83.3; P=0.02). The most frequent adverse event in the nerandomilast groups was diarrhea, reported in 41.3% of the 18-mg group and 31.1% of the 9-mg group, as compared with 16.0% in the placebo group. Serious adverse events were balanced across trial groups.ConclusionsIn patients with idiopathic pulmonary fibrosis, treatment with nerandomilast resulted in a smaller decline in the FVC than placebo over a period of 52 weeks. (Funded by Boehringer Ingelheim; FIBRONEER-IPF ClinicalTrials.gov number, NCT05321069.)